2019
DOI: 10.1515/bmc-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rs9930506 FTO gene polymorphism on obesity risk: a meta-analysis

Abstract: Obesity is associated with polymorphisms of the fat mass and obesity associated gene (FTO). This meta-analysis aimed to investigate the association of the rs9930506 FTO gene polymorphism and obesity. To the best of our knowledge, this study is the first meta-analysis to evaluate the relation between FTO rs9930506 polymorphism and obesity.We searched PubMed, Web of Science, and Embase to identify studies investigating the relations between the rs9930506 FTO gene polymorphism and obesity risk. We pooled adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
1
29
0
1
Order By: Relevance
“…Various studies have shown an association between FTO gene expression with energy expenditure, ghrelin, and leptin hormone levels and the risk of obesity and type 2 diabetes. 30,32,49,50 As well, excessive intake of protein and carbohydrates up-regulated the FTO gene expression and exacerbates the process of obesity in susceptible individuals. 30 Since the knockdown and overexpression of FTO gene can inhibit and increase the differentiation and adipogenesis of adipocytes, it seems that the appropriate adipocyte differentiation and proliferation are associated with FTO gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown an association between FTO gene expression with energy expenditure, ghrelin, and leptin hormone levels and the risk of obesity and type 2 diabetes. 30,32,49,50 As well, excessive intake of protein and carbohydrates up-regulated the FTO gene expression and exacerbates the process of obesity in susceptible individuals. 30 Since the knockdown and overexpression of FTO gene can inhibit and increase the differentiation and adipogenesis of adipocytes, it seems that the appropriate adipocyte differentiation and proliferation are associated with FTO gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The important role of FTO on body composition, and risk of obesity has been proven in children and adults. [29][30][31][32] According to different studies, FTO has an important role in the association between amino acid levels and mTORC1 function, so that inappropriate FTO gene leads to weakness of mTORC1 signaling pathway. 33,34 Also, it seems that the FTO gene has an important role in the proliferation and differentiation of cells through PI3K/Akt signaling pathway and can perform a critical role in the relationship between 5′ AMP-activated protein kinase (AMPK) with the PI3K/AKT/mTOR pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Three genes were analyzed. FTO, whose polymorphisms are strongly associated with obesity and fat mass, exerts the greatest influence on BMI of all known genes [66]. PLIN1 is also associated with an excessive bodyweight risk and complications of obesity (e.g., insulin resistance or different metabolic disorders) [67].…”
Section: Resultsmentioning
confidence: 99%
“…It codes the enzyme alphaketoglutarate dioxygenase responsible for the demethylation of numerous nucleic acid molecules. The latest metaanalyses confirm that the adverse variants of the FTO gene polymorphism are significantly related to obesity [24]. On the other hand, dietary interventions has the same effect, irrespective of one's polymorphic variants, which suggests that environmental interventions and lifestyle prevail over the innate genetic variability [25].…”
Section: Ftomentioning
confidence: 99%